ROLE OF THE EFL TEACHER IN THE EDUCATIONAL PROCESS - Ataboyev, Isroil; Rustamov Ilkhom Tursunovich, (Журнал иностранных языков и лингвистики, 2023)
In our article, he studied the role of English Language teachers in facilitating learning in the EFL class. The study found that English teachers play six roles in their classes. My roles are facilitator, manager, appraiser, resource, participant, and consultant. The role of an English teacher does little to promote the student's autonomy.